Changes in Biochemical Composition and Energy Reserves Associated With Sexual Maturation of Octopus maya - Pascual, Cristina; Cruz-Lopez, Honorio; Mascaró, Maite; Gallardo, Pedro; Sánchez, Ariadna; Domingues, Pedro; Rosas, Carlos (Frontiers in Physiology, 2020)
Climate conditions are related to changes in the biochemical composition of several tissues and associated to the processes of growth and sexual development in cephalopods. The biochemical composition (protein, glucose, cholesterol, acylglycerides) and hemocytes of the hemolymph, the hepatosomatic and gonadosomatic indices, and the reserves of the gonad, hepatopancreas and muscle (lipids, glycogen, and caloric value of muscle) of Octopus maya were determined and related to sex and season. A total of 154 wild animals were used (≈50 caught per season) and the multivariate analysis of the biochemical indicators of the tissues allowed following the variations during winter, dry and rainy season. The permutational MANOVA showed that both sex and season contributed significantly to variations in metabolites and energy reserves. However, the non-significant interaction term indicated that the biochemical composition changed with the seasons in a similar way and regardless of sex. The pattern observed in metabolites and reserves indicates a variation associated with growth and the reproductive peak, but may also reflect a physiological response to seawater temperature. The present study provides reference values for several physiological indicators in O. maya that may be useful for programs monitoring wild populations, as well as to design diets and management protocols to produce octopus under controlled conditions.